EVERYDAY POLITICS OF ONLINE OJEK DRIVERS: TAKING COVER AND FIGHTING APPLICATORS FROM THE COMMUNITY BASECAMP - Nadir, Sakinah; Sunardi, Sunardi (Sosiohumaniora, 2024)
The platform-based transportation business model has swept across almost all regions in Indonesia. Millions of workers have been absorbed into the workforce in this business model. However, the lack of government protection, compounded by the absence of regulations governing working conditions and safety for workers, often leads to working conditions that favor the applicator side. In this less-than-ideal situation, some workers (online motorcycle taxi drivers) have formed online motorcycle taxi communities as an alternative to cope with these less-than-ideal conditions. This article will look at how the online motorcycle taxi community is used as a medium of indirect resistance against applicators. Using a qualitative method, we adopt Browney Frey's (2020) framework on how the vulnerability of the platform workforce is produced by exploring the online motorcycle taxi community and resistance in Indonesia. Data collection is conducted through interviews and observations. We interviewed at least two communities and more than six drivers. This article argues that the organization of online motorcycle taxis that are formed through the community is part of political expression to get security guarantees. At a certain level, the existence of the community is used as a covert medium of everyday resistance. This fieldwork took place in Palu, Central Sulawesi. This article contributes to understanding the nature of organizers and models of workers' resistance to flexible work regimes sponsored by digital work platforms.